Rural-Urban Migration in Developing Countries Lessons from the Literature - Selod, Harris (The World Bank, 2021)
This paper reviews the recent literature on rural-urban migration in developing countries, focusing on three key questions: What motivates or forces people to migrate?What costs do migrants face? What are the impacts of migration on migrants and the economy? The literature paints a complex picture whereby rural-urban migration is driven by many factors and the returns to migration as well as the costs are very high. The evidence supports the notion that migration barriers hinder labor market adjustment and are likely to be welfare reducing. The review concludes by identifying gaps in current research and data needs